Contents Page Format in Scientific Journals Effect on Efficiency and Ease of Scanning - Kallner, H.; Modan, M.; Modan, B.; Wolman, M. (Methods of Information in Medicine, 1977)
The effect of contents page format on the efficiency and ease of scanning by 54 medical scientists, was tested using 14 different format patterns. Significant differences were found between formats with respect to speed of scanning, rate of missed key words, and subjective appeal to the reader. These three criteria were not necessarily related, but some formats were better than others in all three. The results seem to indicate that when the material directly related to the immediate purpose of the scanner is separated from unrelated material, such as in a separate column, and when the unrelated material is more concentrated spatially, efficiency of scanning is increased. Study of newly devised formats may lead to an optimal one with considerable gain in total scanning time and rate of key words located, as well as reduction in fatigue.
Keywords: Contents Page; Scanning Efficiency; Printed Format Perception